PERAN GURU PENDIDIKAN AGAMA ISLAM BERBASIS KULTUR PESANTREN DALAM INTERNALISASI KARAKTER RELIGIUS SISWA MADRASAH - Didik Tamamul Iman; Muhammad Haris; Adi Haironi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Religious character education plays a strategic role in shaping the personality of Madrasah Aliyah students, particularly during adolescence, which represents a critical stage of moral and spiritual development. Islamic Religious Education teachers serve as the central actors in the process of internalizing religious values, especially when education is implemented within a pesantren-based cultural environment. This study aims to describe and analyze in depth the role of Islamic Religious Education teachers integrated with pesantren culture in shaping students’ religious character at MA Al Manshur Al Islamy Kediri. This research employs a qualitative approach with a descriptive research design. Data were collected through observations of learning activities and religious practices, in-depth interviews with teachers and students, and documentation of school programs and policies. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation. The findings reveal that Islamic Religious Education teachers function as educators, role models, spiritual mentors, religious motivators, and reinforcers of pesantren culture. The internalization of religious character is implemented through habituation of worship practices, cultivation of Islamic manners and behavior, integration of pesantren values into learning activities, and application of religious discipline in daily life.